Pengembangan Media Pembelajaran Bahasa Indonesia Berbasis Game Edukasi Berbantu Canva Dalam Kurikulum Merdeka - Friska, Sonia Yulia; Salahuddin, Amar; Rosada, Amrina (Institut Agama Islam Daruttaqwa Gresik, 2023)
This research is motivated by the low learning outcomes of students in learning Indonesian. The low learning outcomes are due to the unavailability of more interesting teaching materials to help students understand learning, this makes student learning outcomes low. To overcome this, researchers are trying to develop teaching materials in the form of educational game-based Indonesian language learning media in class IV SD Negeri Koto Baru that are valid, practical, and effective. This type of research is developed using the ADDIE development model which consists of the analysis stage (Analysis), the planning stage (Design), the development stage (Development), the implementation stage (Implementation), and the evaluation stage (Evaluation). The results of the validation assessment of Indonesian learning educational games on the validity test by three validators who have an average of 89.58% are included in the very valid category, meaning that the educational game is in accordance with the content, graphic feasibility, and language. The practicality test with an average of 92.33% is categorized as very practical, meaning that educational games can be used easily in the learning process. While the effectiveness results with an average of 84% are categorized as very effective, meaning that this educational game can improve student learning outcomes.